2019
DOI: 10.4314/ahs.v19i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Merozoite Surface Protein 1 (msp1) and 2 (msp2) genes and multiplicity of Plasmodium falciparum infection across various endemic areas in Senegal

Abstract: Introduction: Despite a significant decline in Senegal, malaria remains a burden in various parts of the country. Assessment of multiplicity of Plasmodium falciparum infection and genetic diversity of parasites population could help in monitoring of malaria control.Objective: To assess genetic diversity and multiplicity of infection in P. falciparum isolates from three areas in Senegal with different malaria transmissions. Methods: 136 blood samples were collected from patients with uncomplicated P. falciparum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
(58 reference statements)
4
8
0
Order By: Relevance
“…It was observed that 17 allelic variants of msp-1 and 16 of msp-2 were present in the studied areas. This result is in comparison with a similar study from the south of Pakistan (Ghanchi et al, 2010), Iran, South Africa, Myanmar, Sudan, Senegal, andThailand (Heidari et al, 2007;Soe et al, 2017;Somé et al, 2018;Ndiaye et al, 2019;Eltayeb et al, 2020). However, in two southern districts Bannu and Kohat of Khyber Pakhtunkhwa, less allelic variants of P. falciparum were reported (Khatoon et al, 2010;Khatoon et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…It was observed that 17 allelic variants of msp-1 and 16 of msp-2 were present in the studied areas. This result is in comparison with a similar study from the south of Pakistan (Ghanchi et al, 2010), Iran, South Africa, Myanmar, Sudan, Senegal, andThailand (Heidari et al, 2007;Soe et al, 2017;Somé et al, 2018;Ndiaye et al, 2019;Eltayeb et al, 2020). However, in two southern districts Bannu and Kohat of Khyber Pakhtunkhwa, less allelic variants of P. falciparum were reported (Khatoon et al, 2010;Khatoon et al, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Overall, the number of different alleles for msp-1 and msp-2 found in the three sites (18 and 40, respectively) con rms a high level of malaria transmission in Madagascar. These numbers are comparable to those found in Africa such as in Nigeria, the Republic of Congo, the Central African Republic, the Equatorial Guinea or Senegal [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 80%
“…In the areas of high malaria transmission, there is an increase of Plasmodium diversity and MOI in non-pregnant individuals [ 16 , 17 ]. In addition, some studies reported an association between PAM and highly polymorphic parasites and multiclonal parasites [ 18 , 19 ], while others showed the reverse [ 20 , 21 ]. However, only few studies have been carried out on the genetic diversity of P. falciparum in Congolese pregnant women [ 22 ], and none of these reports has investigated their relationship with poor pregnancy outcomes, such as maternal anaemia, low birth weight, and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%